Safety Assessment of Lactiplantibacillus plantarum TWK10 Based on Whole-Genome Sequencing, Phenotypic, and Oral Toxicity Analysis - Han-Yin Hsu; Yi-Chu Liao; Shih-Hsuan Lin; Jin-Seng Lin; Chia-Chia Lee; Koichi Watanabe (Microorganisms, 2022)
Lactiplantibacillus plantarum TWK10 (TWK10), isolated from Taiwanese pickled cabbage, has been demonstrated to exert beneficial probiotic effects in both mice and humans. Here, we comprehensively assessed the safety of TWK10 using both in vivo and in vitro approaches, including whole-genome sequence analysis, an assessment of hemolytic activity, and performing an antimicrobial susceptibility test, the Ames bacterial reverse mutation assay, the chromosomal aberration test, a rodent peripheral blood micronucleus test, and the 28-day subacute oral toxicity assay. The results showed that there was no significant increase in the incidence of reverse mutations or chromosomal aberrations following exposure to TWK10. Moreover, no significant changes were detected either in the number of reticulocytes or the incidence of micronuclei in ICR mice, and no subacute toxicity was recorded in SD rats at the oral TWK10 dosage of 2000 mg/kg body weight/day repeated for 28 days. Additionally, TWK10 exhibited no hemolytic activity and was susceptible to all the antibiotics tested, except kanamycin. However, no antimicrobial resistance genes, virulence factors, or genes involved in biogenic amine synthesis were found in the genome of TWK10. Our findings demonstrated that TWK10 has high potential of being safe for human consumption as a probiotic.